Management of chronic primary pelvic pain syndromes. (27th October 2021) - Parsons, Brian A.; Baranowski, Andrew P.; Berghmans, Bary; Borovicka, Jan; Cottrell, Angela M.; Dinis‐Oliveira, Paulo; Elneil, Sohier; Hughes, John; Messelink, Bert E. J.; de C Williams, Amanda C.; Abreu‐Mendes, Pedro; Zumstein, Valentin; et al.
Abstract : Management of chronic pelvic pain (CPP) remains a huge challenge for care providers and a major burden for healthcare systems. Treating chronic pain that has no obvious cause warrants an understanding of the difficulties in managing these conditions. Chronic pain has recently been accepted as a disease in its own right by the World Health Organization, with chronic pain without obvious cause being classified as chronic primary pain. Despite innumerable treatments that have been proposed and tried to date for CPP, unimodal therapeutic options are mostly unsuccessful, especially in unselected individuals. In contrast, individualised multimodal management of CPP seems the most promising approach and may lead to an acceptable situation for a large proportion of patients. In the present review, the interdisciplinary and interprofessional European Association of Urology Chronic Pelvic Pain Guideline Group gives a contemporary overview of the most important concepts to successfully diagnose and treat this challenging disease.